Construção de cenários de regime de chuvas no estado do Ceará: aplicabilidade de análise de Fourier - Nogueira, Marcelo Leão (2011)
Located in the Northeast of Brazil, the state of Ceará has a different climatical system from other regions, and it has been widely studied about the peculiar rain regime . To undesrtand that regime, the state was divided into homogeneous rain macro-regions for the studies done by Fundação Cearense de Meteorologia e Recursos Hídricos (FUCEME). In order to characterize and build possible sceneries related to the rain level, pluviometrical places were selected in those macrorregiões to apply a mathematical tool called Fourier Analysis, which helps to turn the data of a time series into frequency data, what allows to verify the behavior of the variability in each macro-regions. Results based on the precipitation data of the selected places have showed that the tool is effective in the characterization of the region in climatical studies, briefly indicating thatcreating for regions closer to the shore, the frequency curve has less irregular features. The eastern places are a little similar in their variability, although they are in different macro-regions. When it comes to the macro-region in the Central Countryside, the results showed that the place had a peculiar feature, and a speficic study for that region was suggested. The Fourier Analysis also creates possible sceneries related to the pluviometrical level in the next years. Nevertheless, the sceneries studied presented high level of variation in their behaviour, indicating years of extreme scarcity, and right after that extreme abundance in relation to the average of the rain level in that region. That variation may be explained by the high pluviometrical variability rate, which occurs every year in the state of Ceará. It is also relevant to point out that the Fourier Analysis seems to be a consistent tool in its methodology and may show satisfying results dependin on the variables and the circumstances.